2018
DOI: 10.1186/s41205-018-0037-4
|View full text |Cite
|
Sign up to set email alerts
|

3D printing of surgical hernia meshes impregnated with contrast agents: in vitro proof of concept with imaging characteristics on computed tomography

Abstract: BackgroundSelected medical implants and other 3D printed constructs could potentially benefit from the ability to incorporate contrast agents into their structure. The purpose of the present study is to create 3D printed surgical meshes impregnated with iodinated, gadolinium, and barium contrast agents and characterize their computed tomography (CT) imaging characteristics. Commercial fused deposition layering 3D printing was used to construct surgical meshes impregnated with imaging contrast agents in an in v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 27 publications
0
31
0
2
Order By: Relevance
“…The present study showed feasibility of 3D printing screws, plating, and other constructs impregnated with drugs, and profiled the mechanical properties effect of incorporating these drugs into the 3D printed constructs. The drug impregnating capabilities are similar to prior in vitro studies that incorporated antibiotics and chemotherapeutics into 3D printed constructs [8,9,11,15,16,17]. Several studies have shown antibiotics and chemotherapeutics incorporated into 3D printed filaments, catheters, and meshes [9,11,15].…”
Section: Discussionmentioning
confidence: 56%
“…The present study showed feasibility of 3D printing screws, plating, and other constructs impregnated with drugs, and profiled the mechanical properties effect of incorporating these drugs into the 3D printed constructs. The drug impregnating capabilities are similar to prior in vitro studies that incorporated antibiotics and chemotherapeutics into 3D printed constructs [8,9,11,15,16,17]. Several studies have shown antibiotics and chemotherapeutics incorporated into 3D printed filaments, catheters, and meshes [9,11,15].…”
Section: Discussionmentioning
confidence: 56%
“…Some preliminary work has been done about the use of 3D printing for mesh implant manufacture. However, these works were not realistic as they propose the use of materials such as PLA or PCL that are biodegradable and do not present appropriate mechanical properties for this task [38,48,49]. Some of these works incorporated some antibiotics to the material.…”
Section: Discussionmentioning
confidence: 99%
“…These stents were successfully modified with barium contrast to create x-ray attenuation, an important factor for fluoroscopic visualization and localization during endoscopic procedures. A prior study of impregnated contrast materials showed barium to be more resilient than iodinated contrast materials when incorporated into the structure of 3D-printed constructs (i.e., surgical mesh used in that study) [22]. Additional PCL and other polymer coatings or drugs could be applied to PVA-based stents for a variety of material modifications including increased mechanical properties, enhanced cell attachment, and optimal drug delivery.…”
Section: Discussionmentioning
confidence: 99%
“…Cytocompatible, hydrophilic, and drug-deliverable 3D printed materials and techniques have been recently explored and hold great promise in cell culture models, medical devices, and tissue-engineered substrates [22,23,24,25]. Such materials include 3D printed polyvinyl alcohol (PVA), a water soluble polymer.…”
Section: Introductionmentioning
confidence: 99%